Site characterization of reclaimed lands based on seismic cone penetration test - Wang, Hao (2022)
Seismic cone penetration test (SCPTu) has been used for the determination of seismic velocities and the corresponding stiffness parameters of intact soils. In this study, SCPTu tests are carried out at three reclaimed land sites in Singapore for characterizing the reclaimed fill and the underlying marine clay. New methods for interpreting the downhole-type shear wave velocity, Vs, are adopted. The calculation method for Vs considering the Snell's law instead of the straight ray assumption is recommended for reclaimed lands. The existing CPTu- and SCPTu-based interpretation methods for the unit weight and the preconsolidation stress of both sand and clay are examined, and new interpretation methods for the cohesive fill are proposed. Using the SCPTu data, new correlations between Vs and routine CPT measurements for the sand fill, the cohesive fill and the marine clay are also proposed. The derived correlations for the fill materials are found to be significantly different from those proposed for intact soils in literature, mainly due to the difference in geological history and material composition. The application of the new correlations is illustrated through three independent case studies. The proposed correlations provide alternative methods for valuable insights into the stress and state dependence of the engineering properties of the reclaimed fill and serve as an efficient and economical way of obtaining engineering parameters at reclaimed lands.